Impaired Sensitivity to Thyroid Hormones Is Associated With the Change of Abdominal Fat in Euthyroid Type 2 Diabetes Patients: A Retrospective Cohort Study - Bin Cao; Kun Li; Jing Ke; Dong Zhao (Journal of Diabetes Research)
Conclusion: Impaired central sensitivity to thyroid hormones was significantly associated with the reduction of VFA and SFA, while impaired peripheral sensitivity was associated with an increase of SFA in euthyroid individuals with T2DM.